2021
DOI: 10.1590/s1984-29612021006
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone, chloroquine, primaquine, quinine and tetracycline: antiproliferative effects of relevant antimalarials on Neospora caninum

Abstract: Neospora caninum is an apicomplexan parasite that causes abortion in cattle, resulting in significant economic losses. There is no commercial treatment for neosporosis, and drug repositioning is a fast strategy to test possible candidates against N. caninum. In this article, we describe the effects of atovaquone, chloroquine, quinine, primaquine and tetracycline on N. caninum proliferation. The IC50 concentrations in N. caninum were compared to the current information based on previous studies for Plasmodium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…Consistent with previously published studies [22][23], atovaquone had an IC 50 value of 0.004 ± 0.0007 µM and pyrimidine had an IC 50 value of 0.314 ± 0.1040 µM. To assess the cytotoxicity of these drugs on HFF cells, dilutions of the drugs were sequentially added to the HFF cells and cell viability was determined using CCK-8 reagent.…”
Section: Determination Of the Sensitivity Of Nc1-luc To Known Drugssupporting
confidence: 73%
See 3 more Smart Citations
“…Consistent with previously published studies [22][23], atovaquone had an IC 50 value of 0.004 ± 0.0007 µM and pyrimidine had an IC 50 value of 0.314 ± 0.1040 µM. To assess the cytotoxicity of these drugs on HFF cells, dilutions of the drugs were sequentially added to the HFF cells and cell viability was determined using CCK-8 reagent.…”
Section: Determination Of the Sensitivity Of Nc1-luc To Known Drugssupporting
confidence: 73%
“…The results show that atovaquone and pyrimethamine have dose-dependent inhibitory effects on Nc1-Luc, which can be re ected by a reduced level of luminescent signaling. Pereira et al [22][23] demonstrated that atovaquone and pyrimethamine inhibited the growth of N. caninum with IC 50 values of 0.008 ± 0.002 µM and 0.312 ± 0.017µM, respectively. This is consistent with our ndings, in which atovaquone and pyrimethamine inhibited Nc1-Luc strains with IC 50 values of 0.004 ± 0.0007 µM and 0.314 ± 0.1040 µM, respectively, demonstrating the high susceptibility of Nc1-Luc strains to drug evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations